INFLUENCE OF BREED, AGE, SIZE AND PARITY OF THE DAM ON THE FREQUENCY DISTRIBUTION OF DYSTOCIAS IN CANINES - NARASIMHA , MURTHY; DEVARAJ, M; KRISHNASWAMY, A; HONNAPPA, T G (The Indian Journal of Animal Reproduction, 2023)
The influence of breed, age, size and parity of the bitch on the incidence of dystocia was analyzed. Nearly 30 per cent of dystocia cases presented (n=1236) were either in Labrador Retriever or German Shepards. However, 23.63 per cent of all dystocia encountered were in brachycephalic breeds like Pug, Bull dog and Boxers. The size of the breed was found to have a significant effect on the incidence of dystocia, the incidence being significantly higher in medium and large size breed. It was also observed that the incidence of the dystocia was highest in bitches aged 2-4 years and gradually declined with the advancing age. Bitches less than 4 years accounted for nearly 62 per cent of the dystocia cases suggesting the preference of owners to breed animals at their younger age and withhold breeding in aged animals. In the present study 31.07 per cent of cases referred were primiparous and the rest had delivered 1-8 times. The incidence of dystocia decreased progressively with increase in parity and the least incidence was recorded in animals with more than 5 previous deliveries.